2016
DOI: 10.1021/acs.jpcc.6b10644
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic Mechanical Properties of Black Phosphorus Nanoribbons

Abstract: The mechanical properties of black phosphorus (BP) nanoribbons suspended on narrow grooves are quantitatively investigated with the nanoindentation method on the basis of atomic force microscopy. The elastic moduli of BP nanoribbons are strongly related to the included angle between the lattice orientation and the groove. A theoretical model based on classical elasticity theory is established to explain the directional elastic modulus and matches well with the experimental results. The ideal elastic modulus of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
71
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(75 citation statements)
references
References 44 publications
4
71
0
Order By: Relevance
“…Unlike single-layer 2d-MoS2, both undeformed and deformed phosphorene have orthorhombic (pman) layer group symmetry with distinct structural anisotropy that translates into anisotropy of mechanical, electrical, and optical properties. 37,38,[51][52][53][54][55] As can be seen in Figure 3, unstrained phosphorene is a semiconductor with computed near-direct band gap of 0.79 eV. Here, the CBM and VBM are at Γ point and Γ-Y symmetry line near Γ point, respectively, in good agreement with previous studies.…”
Section: Strain-induced Effects In Phosphorenesupporting
confidence: 89%
“…Unlike single-layer 2d-MoS2, both undeformed and deformed phosphorene have orthorhombic (pman) layer group symmetry with distinct structural anisotropy that translates into anisotropy of mechanical, electrical, and optical properties. 37,38,[51][52][53][54][55] As can be seen in Figure 3, unstrained phosphorene is a semiconductor with computed near-direct band gap of 0.79 eV. Here, the CBM and VBM are at Γ point and Γ-Y symmetry line near Γ point, respectively, in good agreement with previous studies.…”
Section: Strain-induced Effects In Phosphorenesupporting
confidence: 89%
“…For each thickness, the thermal conductivity anisotropy ratio between ZZ and AC is constant around 2. This ratio is comparable to that of Young's modulus between ZZ and AC summarized in Figure b, where the first‐principles calculation and experimental measurement results are compared. The overall simulated Young's modulus, even for single layer phosphorene, is comparable to that of experimentally measured data and its ratio between ZZ and AC is around 2.2 ± 0.6.…”
supporting
confidence: 75%
“…First, BP nanosheets have higher mechanical strength. The ideal elastic moduli of zigzag and armchair BP nanoribbons are approximately 65 and 27 GPa, respectively [26]. Morenomoreno et al [67] investigated the effects of environmental conditions on the mechanical properties of few-layer BP, and the results indicated that the elastic modulus and the breaking strength of BP nanosheets were 46 ± 10 GPa and 2.1 ± 1 GPa, respectively.…”
Section: Potential Of Bp As Lubricantsmentioning
confidence: 99%